Análisis de las técnicas de extracción de ADN en piezas dentales con fines identificativos forenses. - Rodríguez Inca, Víctor Patricio (2022)
The dentist often occupies an important place in forensic medical sciences, as he stands out in several areas such as identification, reconstruction of events and crime resolution, his professional services linked to optimal body identification techniques allow reducing time and costs. in the recognition of corpses, whatever the cause of death of the individual, since the elements analyzed, such as the teeth, are the last to be destroyed, the study based its search for information on a systematic bibliographic review with the objective of identifying which is the optimal DNA technique for the identification of corpses, the results showed that the decalcification of the genetic material was detected as the most efficient since it managed to discover 98% of the cases by superimposing techniques such as: organic extraction, DNA washing in columns of hydroxyapatite and use of Silica.